Newborn hearing screening results in an inner part of Aegean region - Özbay, İsa and Kucur, Cüneyt and Oğhan, Fatih and Aksoy, Sinan and Erdoğan, Onur and Tuğrul Karakuş, Yasin (ENT Updates, 2014)
Objective: To investigate hearing loss ratio of babies screened at our university hospital which is reference hospital in Kütahya, Turkey Methods: A total number of 6881 newborns were screened for hearing between February 2010 and December 2013 in our hospital. Screening was done before newborns discharged. The parents of the newborns discharged during holidays were asked to come within 15 days. A three-stage screening protocol was implemented consisting of an initial screening with transient evoked otoacoustic emissions (TEOAE) followed by a second-stage screening also with TEOAE and screening auditory brainstem response (ABR). Babies who had unilateral or bilateral referrals with TEOAE and screening ABR were referred to other clinics which have clinical ABR. Babies were divided into 2 groups by means of having risk factors and not having risk factors. Results: Out of 6881 newborns, 33 (0.47%) of them had hearing loss consisting of 21 (0.3%) patients had bilateral hearing loss and 12 (0.17%) patients had unilateral hearing loss. Conclusion: Newborn hearing screening tests should be done throughout the country and the babies with hearing loss should be identified before permanent damages occur so that these patients can be productive people for society.